2008
DOI: 10.1165/rcmb.2007-0418oc
|View full text |Cite
|
Sign up to set email alerts
|

MD-2–Dependent Pulmonary Immune Responses to Inhaled Lipooligosaccharides

Abstract: Endotoxins represent one of the most potent classes of microbial immunoactive components that can cause pulmonary inflammation. The aim of this study was to compare the inflammatory potency of two types of Neisseria meningitidis endotoxins (lipooligosaccharides) in lungs: wild type (hexaacylated, LOS wt ) and mutant type (pentaacylated, LOS msbB ), and to determine the importance of MD-2 in endotoxin responses in lungs in vivo. Endotoxin-normoresponsive mice (BALB/c) were exposed to selected doses of penta-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 40 publications
2
57
1
Order By: Relevance
“…In this study, we postulated that the engagement of the innate immune system of the respiratory tract mucosa by the LOS of commensal Neisseria may elicit a weak response, thereby promoting persistent colonization. This concept is supported by the recent report that meningococcal LOS with hexaacylated LA was significantly more inflammatory in the lungs of an in vivo mouse model than LOS with pentaacylated LA (25). In addition, the study also suggested that, although bacterial products and cytokines can upregulate MD-2, low expression levels of MD-2 in the airway epithelia play a role in the respiratory response to neisserial LOS (29).…”
supporting
confidence: 60%
“…In this study, we postulated that the engagement of the innate immune system of the respiratory tract mucosa by the LOS of commensal Neisseria may elicit a weak response, thereby promoting persistent colonization. This concept is supported by the recent report that meningococcal LOS with hexaacylated LA was significantly more inflammatory in the lungs of an in vivo mouse model than LOS with pentaacylated LA (25). In addition, the study also suggested that, although bacterial products and cytokines can upregulate MD-2, low expression levels of MD-2 in the airway epithelia play a role in the respiratory response to neisserial LOS (29).…”
supporting
confidence: 60%
“…Brix and colleagues suggested that distinct forms of endotoxin may trigger TLR4 differently, with the result that the pentaacylated endotoxin is protective against asthma and allergic sensitization and the more common hexaacylated variety poses increased risk (35). Likewise, Hađina and colleagues noted lower inflammation and differing cytokine profiles in mice exposed to pentaacylated versus hexaacylated forms of endotoxin (36). Predictors of endotoxin in house dust have been examined in several previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hapina et al [34 ] evaluated the dose-dependent pulmonary inflammatory potency of two types of endotoxin from Neisseria meningitides, a lipooligosaccharide (LOS). Wild type hexaacylated endotoxin (LOS wt ) and mutant pentaacylated endotoxin (LOS msbB ) were administered by intranasal inhalation to mice.…”
Section: Exposure To Endotoxin In Micementioning
confidence: 99%
“…Hadina et al [34 ] then evaluated responsiveness to MD-2 null mice versus MD-2 competent mice. Inhalation of hexaacylated LOS in MD-2 À/À mice failed to induce neutrophil recruitment or cytokine upregulation demonstrating the importance of MD-2 in endotoxin responsiveness in vivo.…”
Section: Exposure To Endotoxin In Micementioning
confidence: 99%